Exploring Content-Based Syllabus For Indonesian EFL Nursing Students At Politeknik Kesehatan Makassar - Baharuddin Kordja; Muhammad Basri; St Rahmatia; Ismail Ismail; Nasrullah Nasrullah (Pascasarjana Universitas Negeri Makassar, 2022)
The objective of the study was to explore the most appropriate content-based syllabus for EFL nursing students and to identify the suitable and relevant topics to the language learning process at Politeknik Kesehatan Makassar. The study employed quantitative descriptive approach. The samples were fourth semester students of Nursing Department, English lecturers and nurses at Wahidin Sudirohusodo Hospital Makassar. The total sample of this study was 50 respondents which were selected based on purposive sampling techniques. The researcher took 40 nursing students, 5 English lecturers, and 5 senior nurses who were experienced in foreign countries. The collection of data was done by distributing the questionnaires to the respondents to identify the students’ needs to attend the Nursing Department and their objective or their experiences, and also to discover their mastery level on the competencies needed and the main priority of competencies. The data was analyzed by applying descriptive statistics The findings of the study indicated that the appropriate syllabus for Nursing Students at Politeknik Kesehatan Makassar is the topical syllabus which is organized by the topics or themes. The suitable topics consisted of content-subjects, general subjects, and suggested subjects. The present study provides empirical data on a successful